Genetic polymorphisms associated with the risk of concussion in 1056 college athletes: a multicentre prospective cohort study. Issue 3 (16th September 2017) - Terrell, Thomas Roland; Abramson, Ruth; Barth, Jeffery T; Bennett, Ellen; Cantu, Robert C; Sloane, Richard; Laskowitz, Daniel T; Erlanger, David M; McKeag, Douglas; Nichols, Gregory; Valentine, Verle; Galloway, Leslie
Abstract : Background/aim: To evaluate the association of genetic polymorphisms APOE, APOE G-219T promoter, microtubule associated protein(MAPT)/ tau exon 6 Ser 53 Pro, MAPT/ tau Hist 47 Tyr, IL-6 572 G/C and IL-6R Asp 358 Ala with the risk of concussion in college athletes. Methods: A 23-centre prospective cohort study of 1056 college athletes with genotyping was completed between August 2003 and December 2012. All athletes completed baseline medical and concussion questionnaires, and post-concussion data were collected for athletes with a documented concussion. Results: The study cohort consisted of 1056 athletes of mean±SD age 19.7±1.5 years, 89.3% male, 59.4% Caucasian, 35.0% African-American, 5.6% other race. The athletes participated in American football, soccer, basketball, softball, men's wrestling and club rugby. A total of 133 (12.1% prevalence) concussions occurred during an average surveillance of 3 years per athlete. We observed a significant positive association between IL-6R CC (p=0.001) and a negative association between APOE 4 (p=0.03) and the risk of concussion. Unadjusted and adjusted logistic regression analysis showed a significant association between IL-6R CC and concussion (OR 3.48; 95% CI 1.58 to 7.65; p=0.002) and between the APOE4 allele and concussion (OR 0.61; 95% CI 0.38 to 0.96; p=0.04), which persisted after adjustment for confounders. Conclusions: IL-6R CC was associated with a three times greater concussion risk and APOE 4 with a 40% lower risk.